New Frontiers in Information and Software as Services Service and Application Design Challenges in the Cloud - Agrawal, Divyakant; Candan, K. Selçuk; Li, Wen-Syan (Lecture Notes in Business Information Processing, 2011)
The increasing costs of creating and maintaining infrastructures for delivering services to consumers have led to the emergence of cloud based third party service providers renting networks, computation power, storage, and even entire software application suites. On the other hand, service customers demand competitive pricing, service level agreements, and increased flexibility and scalability. Service consumers also expect process and data security, 24/7 service availability, and compliance with privacy regulations. This book focuses on such challenges associated with the design, implementation, deployment, and management of data and software as a service. The 12 papers presented in this volume were contributed by leaders in academia and industry, and  were reviewed and supervised by an expert editorial board. They describe cutting-edge approaches in areas like service design, service security, service optimization, and service migration.